The Cooperation of Nature and Nurture on Developing Meta-cognitive Abilities in Adolescents_ Gender-Based Function. - Maachi, Fatma (My University, 2017)
Gender differences in spatial abilities overlooked findings generated by the metatheory of evolutionary psychology. This oversight reflects an underlying hostility within the social sciences towards the use evolutionary theory in the study of human behaviour and cognition. As a remedy, this paper outlines the theoretical background of evolutionary psychology, focusing on the insights evolutionary psychology offers for cognitive gender differences research, with particular reference to gender differences in spatial abilities, memory, selfesteem, and linguistic interpretation and performance.
Case Study of Third Grade Secondary Students at High School in Tiaret
Keywords: Left brain right brain functions; Hormones; Cognitive abilities; Parentings styles